2008
DOI: 10.1007/s12011-008-8263-z
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Levels in First-Degree Relatives of Diabetic Patients

Abstract: The present study was conducted to evaluate the serum selenium levels in first-degree relatives of diabetic patients (FDR) according to controls. Insulin resistance, serum lipid levels, inflammation markers, and blood pressure were also studied in these patients. Serum levels of selenium in FDR were significantly lower than control group (74.65 +/- 5.9 vs 88.7 +/- 8.7 microg/dl, p < 0.0001). HsCRP, HOMA-IR, insulin, homocysteine levels were significantly higher in FDR according to the control group (1.32 +/- 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Similar findings were observed in the French EVA cohort study [7] wherein the investigators illustrated that participants with higher Se levels (median plasma levels 104 μg/L) were better protected from oxidative stress and progression of IR as compared to those with lower Se levels (median plasma levels 71 μg/L). Our observations are also in corroboration with studies by Kornhauser et al [19] reporting a deficiency in diabetes together with increased oxidative stress and Ozkaya et al [20] showing a deficiency in first-degree relatives of diabetic patients. However, a longitudinal cohort study by Gao et al [4] indicated no substantial association of selenium status with incidence of diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…Similar findings were observed in the French EVA cohort study [7] wherein the investigators illustrated that participants with higher Se levels (median plasma levels 104 μg/L) were better protected from oxidative stress and progression of IR as compared to those with lower Se levels (median plasma levels 71 μg/L). Our observations are also in corroboration with studies by Kornhauser et al [19] reporting a deficiency in diabetes together with increased oxidative stress and Ozkaya et al [20] showing a deficiency in first-degree relatives of diabetic patients. However, a longitudinal cohort study by Gao et al [4] indicated no substantial association of selenium status with incidence of diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…It was reported that hair Se were negatively correlated with the HOMA-IR controlled for age and sex in a small Korean study [28]. A weak negative correlation between serum Se level and HOMA-IR was found in first-degree relatives of diabetic patients in Turkey [29]. However, in a Swedish study including 1024 elderly men, serum Se level was not associated with insulin resistance after adjusting for age, BMI, cigarette smoking, leisure time physical activity and education [23].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance is not only a hallmark but also a pathogenic factor of T2DM. However, the quantitative relationship between dietary Se intake and insulin resistance has been only reported in studies with very small sample size [28,29] or special groups such as metabolic syndrome (MS) [30], obesity [31,32] and polycystic ovary syndrome (PCOS) patients [33]. A study with large sample size and a wide range of insulin resistance and dietary Se intake in a general population is required in order to understand the association between the two factors.…”
Section: Introductionmentioning
confidence: 99%
“…Severe Se deficiency is rare, while reduced Se levels are seen in diabetics together with increased oxidative stress. In offsprings of diabetic patients Se correlates inversely with CRP and with insulin resistance if Se levels are below 80 μg/l [118]. Excess of Se results in excessive oxidative stress and inflammation as well as diseases like idiopathic scoliosis in adolescents [119] or amyotrophic lateral sclerosis [120].…”
Section: Seleniummentioning
confidence: 99%